THE IMPACT OF HEALTHCARE REGULATIONS AND COMPLIANCE ON HEALTH ADMINISTRATION PRACTICES DURING COVID-19 PANDEMIC - Muhannad Ayidh Alharbi, Saud Alasmri, Hassan Ahmed Abualzawayid, Naif Sulaiman Alsabr, Abdulaziz khulaif Al mutairi, Mansour Ayidh Almutairi, Abdulrahman Mahdi Alzamanan, Abdulrahman Abdullah Otaen,; Nasser Mohammed Alanazi, Abdullah Ayed Almudurra, Ahmed Gurashi Zaeri, Saud Abdullah Alasmri (Chelonian Research Foundation, 2022)
Healthcare waste refers to the waste produced by healthcare institutions, medical labs, and biomedical research institutes. Inadequate handling of this trash presents significant hazards of disease transmission to garbage pickers, waste workers, healthcare professionals, patients, and the whole population due to potential contact with infectious pathogens. Inadequate waste management results in the release of hazardous and detrimental pollutants into the community. Nevertheless, the presence of highly infectious pathogens like the COVID-19 virus has caused significant disruption in the management and recycling of healthcare waste due to the large quantity of trash produced and its contagious properties. Multiple nations have implemented safety protocols to address this pollution and handle medical waste; yet, these procedures are inadequate and differ based on the specific circumstances of each country. Furthermore, the World Health Organization (WHO) has established explicit instructions for the handling and disposal of healthcare waste. These rules are assisting in the management of the highly transmissible healthcare waste generated by the ongoing epidemic. Effective healthcare waste management may contribute to mitigating the transmission of the COVID-19 virus and enhancing the potential for recycling materials, rather than disposing of them in landfills. Disinfecting and organizing healthcare waste promotes sustainable management and enables their usage for productive reasons. This paper examines the various tactics used by different nations for managing healthcare solid waste. It also addresses the obstacles encountered in this process and proposes potential solutions to overcome these issues. Additionally, it offers valuable perspectives on the management of hospital solid waste in the context of the COVID-19 epidemic and proposes a potential path for the future. Keywords: Medical waste, Management of healthcare waste, COVID-19 pandemic, challenges, solutions.